A perceptual study of users' expectations of urban green infrastructure in Kalamaria, municipality of Greece. Issue 5 (8th August 2016) - Karanikola, Paraskevi; Panagopoulos, Thomas; Tampakis, Stilianos; Karipidou-Kanari, Aikaterini
Abstract : Purpose: – The purpose of this paper is to investigate residents' perceptions, preferences and satisfaction concerning the urban green infrastructure of Kalamaria, Greece, to evaluate the importance of urban parks for residents' well-being and to suggest management improvements. Design/methodology/approach: – Following a random sampling method, 385 residents were interviewed. Green infrastructure number and size, design suitability, safety, variety and care of plants, noise pollution, facilities for people with disabilities and duration and frequency of visits to green areas were among the considered parameters. Factor and hierarchical log-linear analyses were conducted. Findings: – The existing green spaces were insufficient in number, size and design, and their distribution was unsatisfactory. The facilities and equipment in the green spaces were evaluated as rather mediocre, and most respondents were unsatisfied with the overall planning and management of the green infrastructure in the municipality of Kalamaria. The results indicate that resident's well-being relates to their satisfaction with urban green infrastructure. Frequent and longer visits of green spaces significantly improved the perceived well-being. The residents expressed an intention to pay 20-40 percent more than the average price for a house with a view of a green area. Originality/value: – Public perception surveys enable green infrastructure managers to identify preferred management alternatives and to use this information in an urban planning framework. Local authorities can use the results of the present survey to manage the city's green infrastructure, enhance the city's resilience and anticipate climate change challenges and the future needs of residents.